Potensi Kapsul Bee Pollen Plus Sebagai Food Supplement Inovatif Peningkat Stamina dalam Rangka Pencegahan Penggunaan Doping pada Atlet Makassar : Uji Coba Pada Mahasiswa UKM Sepak Bola - Emilia Utomo; Lia Nurmilatun Saidah; Iin Fadhilah Utami; Sartini Sartini (Hasanuddin University, 2017)
Doping used for stamina enhancement and athletes' performance is actually a medicine that has negative effects on health and potentially causes an addiction. Therefore, it is necessary supplements that can increase the stamina and endurance of an athlete and at the same time could minimize the possibility of doping usage. Bee pollen is one of the products of bees which is rich nutrients. The nutrients content of Bee pollen such as carbohydrates, proteins, lipids, minerals, vitamins, and polyphenols is needed by athletes to increase the endurance and stamina in their activities. To enrich its bioactive components, bee pollen extract and fresh bee pollen powder are combined and called Bee Pollen Plus. The current study was Quasi-Experimental with Non-randomized Pre-Post Test Control Group model design by comparing before and after of bee pollen plus intervention. The preparation of bee pollen plus capsule is started with bee pollen extraction followed by the preparation of bee pollen capsule. By the process, it is obtained 18.48% of rendamen percent. The chemical compound analysis showed the protein, carbohydrate and polyphenol levels of bee pollen plus two times higher than bee pollen powder. The intervention of bee pollen plus capsule was provided for 1 week to the student in football activity unit of Hasanuddin University. The running time, blood pressure, pulse rate, body temperature, and breathing frequency were calculated after physical exercise by using the treadmill. The result obtained shows the increased physical performance especially for running time and pulse rate. It can be concluded that the bee pollen plus capsule has been effective to increase the stamina and endurance of the athlete after physical exercise.Keywords: athlete, doping, bee pollen extract, bee pollen powder, nutrient